ISLAM DAN HAK ASASI MANUSIA DALAM AL-QUR’AN - Salsabila Rahmadhani Fitri; Syifa Nurhabibah Sya’bani; Win Prayoga; Zahra Izzatun Nisa (Melati Institute, 2023)
Islam as a doctrinal concept, puts every human being equal to another human being. There is no distinction between men and women, other than the quality of their faith and their aversion to God almighty. In this article, the compiler tried to express and lay out the rights that each individual should earn according to the human rights concept in Islam that refers to a few verses in the Qur'an. To facilitate the discussion, the compiler referred to the fifth maqashid Shari 'ah concept, hifdzu al-din, hifdzu al-mal, hifdzu al-nafs, hifdzu al- 'aql and hifdzu al-nasl. This study uses the interpretation of maudhu'i by drawing up related and interpreted verses and revealing the verse al-nuzul, as well as the verses in the Qur'an. Islam is a concept of teaching, placing every human being equal to other humans. There is no difference between men and women, other than the quality of their faith and piety to Allah swt. In this article, the author tries to reveal and explain what rights must be obtained by each individual in accordance with the concept of human rights in Islam, which refers to several verses in the Qur'an. To facilitate the discussion, the authors refer to the concept of five maqasid shariah, namely hifdzu al-din, hifdzu al-mal, hifdzu al-nafs, hifdzu al-aql, and hifdzu al-nasl. Researchers use a maudhu'i interpretation approach by collecting related verses and interpreting them, as well as revealing the asbab al-nuzul of related verses, as well as their munasabah with other verses in the Qur'an.